MORPHOMETRIC SURVEYS ON ELEOCHARIS PALUSTRIS (L.) ROEM. ET SCHULT. (CYPERACEAE). THE CONTRIBUTION OF HERBARIUM INVESTIGATIONS TO THE DELIMITATION OF ITS SUBSPECIES AND THEIR DISTRIBUTION IN ITALY - Lastrucci, L.; Lazzaro, L.; Lunardi, L.; Fiorini, G.; Viciani, D. (Annali di Botanica, 2020)
According to the most recent floristic and taxonomic works, Eleocharis palustris (L.) Roem. et Schult. is present in Europe with two subspecies: E. palustris subsp. palustris and E. palustris subsp. waltersii Bureš et Danihelka. Up to now in Italy only the first taxon has been reported in literature, and no specific study was recently carried out to assess the presence of both subspecies on the Italian territory. Accordingly, we conducted a comprehensive analyses of Italian herbarium specimens of E. palustris in order to verify presence and distribution of its subspecies in Italy. Towards these aims we collected a wide set of morphological (glume length and number per cm; spikelet length, culm width, achene length and width, stylopode length and width) and anatomical characters (stomata length) and evaluated their contribution to the differentiation of the two subspecies adopting a classification tree analyses. The analyses lead us to report for the first time in Italy E. palustris subsp. waltersii. This taxon was found to be present in 9 northern and central Italian regions. Our contribution allowed to confirm the presence of E. palustris subsp. palustris in almost all the Italian regions.